Crocetin Protected Human Hepatocyte LO2 Cell From TGF-β-Induced Oxygen Stress and Apoptosis but Promoted Proliferation and Autophagy via AMPK/m-TOR Pathway - Guo, Hongxing; Ruan, Chenyu; Zhan, Xiuhong; Pan, Hao; Luo, Yumei; Gao, Ke (Frontiers in Public Health, 2022)
Object To investigate the protective effects of crocetin against transforming growth factor - β (TGF-β) - induced injury in LO2 cell. Methods Human hepatocyte LO2 cells were pretreated with crocetin (10μM) for 6h, 12h and 24h, and then induced by TGF-β. Proliferation, oxidative stress, apoptosis, autophagy and related proteins were assessed. Results Crocetin pretreating promoted proliferation but suppressed apoptosis in TGF-β-induced LO2 cells. Crocetin protected LO2 cells from TGF-β-induced inflammation and oxygen stress by reducing reactive oxygen species (ROS) and malondialdehyde (MDA) but enhancing superoxide dismutase (SOD) and glutathione (GSH). Autophagy was suppressed in TGF-β but crocetin promoted autophagy in LO2 cells by mediating Adenosine 5'-monophosphate - activated protein kinase (AMPK) / mammalian target of rapamycin (m-TOR) signaling pathway via upregulating p-AMPK and p-Beclin-1 but downregulating p-mTOR. Conclusions Crocetin protected LO2 cell from TGF-β-induced damage by promoting proliferation and autophagy, suppressing apoptosis and anti-inflammation via regulation on AMPK/m-TOR signaling pathway.